The effect of Wise Leadership on Organizational Citizenship Behavior mediation by perceived Organizational support, an analytical study in Al-Imamain Al-Kadhmin Medical City Hospital - Ahmed Quinn Dawood,; Weam Wahhab Alyasiri, (Technium Business and Management, 2025)
The concepts of (wise leadership, perceived organizational support, and organizational citizenship behavior) have received academic attention from researchers, given the scientific and practical importance and the impact of these variables on the performance of organizations, in practical terms, organizational citizenship behavior has been affected by the secretions of the spread of the Corona virus (Covid 19), Which affected the work and behavior of managers and doctors in hospitals, For this reason, the current study aimed: verify the impact of wise leadership on organizational citizenship behavior by mediating perceived organizational support, Doctors and nurses working at Al-Imamain Al-Kadhimiya Medical Hospital were relied upon to apply the study to them, and the size of the study community was (149), the number of responsive and valid sample for statistical analysis was (144), the study included the application of the descriptive analytical approach, the questionnaire tool was used to collect study data, by adopting multiple statistical methods, the results were extracted by adopting a program (SPSS) & (Amos), the most important conclusions of the study included: the impact of wise leadership and its dimensions on both variables (perceived organizational support, organizational citizenship behavior and its dimensions (directed towards the individual, directed towards the organization)), and the lack of impact of wise leadership and its dimensions on the dimension of organizational citizenship behavior directed towards tasks, in addition to showing the dimension of wise leadership (Intellectual intelligence), its lack of impact on organizational citizenship behavior and its dimensions, the results also showed the impact of perceived organizational support on organizational citizenship behavior and its dimensions (directed towards the individual, directed towards the organization), and no effect appeared in the dimension of organizational citizenship behavior directed towards tasks, Finally, the results showed, the presence of a comprehensive and fundamental role for perceived organizational support in mediating the relationship between the impact of wise leadership on organizational citizenship behavior.